On the use of propylene carbonate and dimethyl carbonate as green solvents in organic electrosynthesis - Prudlik, Adrian (2025)
Electroorganic syntheses are often carried out in polar aprotic solvents such as DMF, acetonitrile, or dichloromethane, which exhibit excellent electrochemical properties, but are highly problematic in terms of sustainability. The propylene carbonate–dimethyl carbonate (PC–DMC) system is a promising alternative with enhanced environmental, health, and safety parameters, and has already found numerous applications in electrochemical energy storage systems. Herein, we present a systematic study on the PC–DMC system as reaction medium for organic electrosyntheses, spanning from the characterization of electrolyte properties to representative test reactions on a preparative scale. Anodic synthesis of diaryliodonium salts, cathodic reduction of ketones, and TEMPO-mediated alcohol oxidations serve as use cases, showing that yields are comparable to the ones obtained in conventional solvents. An interesting feature is the possibility for tuning the physicochemical properties of the reaction medium by varying the PC–DMC ratio, which was shown to impact the catalytic rate of TEMPO-mediated alcohol oxidations and the yield of diaryl iodonium synthesis.